Memory Alteration Test to Detect Amnestic Mild Cognitive Impairment and Early Alzheimer’s Dementia in Population with Low Educational Level - Custodio, Nilton; Lira, David; Herrera-Perez, Eder; Montesinos, Rosa; Castro-Suarez, Sheila; Cuenca-Alfaro, José; Valeriano-Lorenzo, Lucía (Frontiers in Aging Neuroscience, 2017)
Background/Aims: Short tests to early detection of the cognitive impairment are necessary in primary care setting, particularly in populations with low educational level. The aim of this study was to assess the performance of Memory Alteration Test (M@T) to discriminate controls, patients with amnestic Mild Cognitive Impairment (aMCI) and patients with early Alzheimer´s Dementia (AD) in a sample of individuals with low level of education. Methods: Cross-sectional study to assess the performance of the M@T (study test), compared to the neuropsychological evaluation (gold standard test) scores in 247 elderly subjects with low education level from Lima-Peru. The cognitive evaluation included three sequential stages: 1) screening (to detect cases with cognitive impairment); 2) nosological diagnosis (to determinate specific disease); and 3) classification (to differentiate disease subtypes). The subjects with negative results for all stages were considered as cognitively normal (controls). The test performance was assessed by means of area under the reciever opereting characteristic curve. We calculated validity measures (sensitivity, specificity and correctly classified percentage), the internal consistency (Cronbach's alpha coefficient), and concurrent validity (Pearson's ratio coefficient between the M@T and CDR scores). Results: The Cronbach's alpha coefficient was 0.79 and Pearson's ratio coefficient was 0.79 (p<0.01). The AUC of M@T to discriminate between early AD and aMCI was 99.60% (sensitivity=100.00%, specificity=97.53%, and correctly classified=98.41%) and to discriminate between aMCI and controls was 99.56% (sensitivity=99.17%, specificity=91.11%, and correctly classified=96.99%). Conclusions: The M@T is a short test with a good performance to discriminate controls, aMCI and early AD in individuals with low level of education from urban settings.